Assessment of effect of climate change on hygrothermal performance of cross-laminated timber building envelope with modular construction. (December 2021) - Chang, Seong Jin; Kang, Yujin; Yun, Beom Yeol; Yang, Sungwoong; Kim, Sumin
Abstract: Cross-laminated timber (CLT) modular construction possesses the advantages of wood, such as excellent carbon storage and thermal insulation, and of modular construction, such as considerably reduced construction period and cost as well as high productivity. This study evaluates the hygrothermal performance of CLT walls considering modular construction in future climatic conditions. Firstly, CLT walls with plywood applied to a core layer were manufactured. A mock-up of a CLT building was produced and its construction process was analyzed. Hygrothermal behavior of the CLT walls was simulated using WUFI simulation program, and the predicted results were verified against measurements obtained from the mock-up experiment. Finally, the hygrothermal performance of the CLT wall was evaluated for four types of insulation and future climate in eight cities of USA. The coefficient of variation—root mean square error (CV(RMSE))—of the temperature and relative humidity inside the ply-lam CLT wall from mock-up experiments and simulation evaluation were 6.43% and 7.02%, respectively, which met the validation criteria. Based on the hygrothermal performance, the ply-lam CLT wall with extruded polystyrene insulation was evaluated as safe from moisture problems in all the eight cities considered in this study. However, the risk of mold growth in all regions and insulation types increased under climate change with a rise of average annual temperature.